2019
DOI: 10.1111/jocn.14795
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with glycaemic control in patients with diabetes mellitus: A systematic literature review

Abstract: Objectives To perform a systematic review search and critically review the empirical evidence concerning the factors affecting glycaemic control in patients with type 1 or 2 diabetes mellitus. Background Previous primary studies have investigated the factors associated with glycaemic control among patients with type 1 or 2 diabetes, but attempts to amalgamate these evidences have been methodologically limited. Hence, a robust review of the evidence is essential to explore factors that can be addressed to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 78 publications
0
43
1
Order By: Relevance
“…However, a meta-analysis of 21 studies on this topic showed a significant improvement of self-efficacy after DSME participation after 6 months,33 indicating that participant’ self-efficacy is increased by DSME participation. Increased self-efficacy seems to be significantly associated with a better glycemic control,34 but more research is needed on how self-efficacy influences glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis of 21 studies on this topic showed a significant improvement of self-efficacy after DSME participation after 6 months,33 indicating that participant’ self-efficacy is increased by DSME participation. Increased self-efficacy seems to be significantly associated with a better glycemic control,34 but more research is needed on how self-efficacy influences glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral research cites a greater preoccupation with food, lack of control over eating high-carbohydrate foods, and food cravings as significant barriers to successful diabetes self-management. [23][24][25][26] Replacing a daily breakfast and afternoon snack with a DSNS can lead to increased overall feeling of control over food choices, perhaps by reducing the uncertainty of eating on glycemic responses. The composition of the DSNS (rich in protein, low glycemic index-carbohydrates and fiber) is more likely to induce changes in gastrointestinal hormones (eg, ghrelin, peptide YY (PYY) and GLP-1) which are known to activate selected corticolimbic regions in the brain typically associated with mood, cognitive function, and food cravings.…”
Section: Discussionmentioning
confidence: 99%
“…Empowerment is a process whereby an individual has greater ability to determine their decisions and self-care activities for their health. 27 In people with DM it is important to have sufficient diabetes-related knowledge in order to increase patients' empowerment. [28][29][30] Several studies have shown that empowerment can reduce the level of HbA1c, endorse behavioural changes, improve psychological status and increase health literacy, self-care and control.…”
Section: Empowerment Of Persons With Dmmentioning
confidence: 99%
“…34 Studies have shown that improved dietary knowledge is associated with better glycaemic control because persons well-equipped with dietary knowledge tend to make informed decisions that are appropriate to their health condition. 27 This is considered to be very important for chronic health diseases as recognised by the World Health Organization (WHO), while keeping or improving persons' quality of life. 35 A patient-centred empowerment-based programme can improve the quality life of persons with poorly controlled DM.…”
Section: Empowerment Of Persons With Dmmentioning
confidence: 99%